تحليل العبارات باللغة العربية في كتاب القصيدة الكلاسيكية (قصيدة البردة) - Sodikin, Akhmat; Qardhwi, Muhammad Yusuf; Indra, Denny (FASAHAH, 2024)
ABSTARCTBushiry's Qasidah Burdah is a compilation of verses praising the Prophet Muhammad. Qasidah Burdah is one of Imam Bushiri's compositions, he is the earliest poem after a very long hiatus. Qasidah Burdah is read and sung widely throughout the Islamic world. The reading of the qasidah is usually interspersed with additional prayers and verses. The choice of diction of words used in this Qasidah makes this Qasidah beautiful. Therefore, the burdah kasidah is much admired by Sufis and other Muslims. Apart from that, the many meanings of idioms used in this Qasidah make researchers interested in finding out the original meaning contained in this Qasidah. The aim of this research is to find out the meaning of the idioms contained in each verse of Qasidah Burdah Bushiri. The type and method of research used is qualitative with text analysis methods to review the qasidah burdah verse in terms of idiom meaning. The results of this research are that in Qasidah Burdah from chapters 1 to chapter 10, researchers found that there are 99 meanings of idioms.مستخلص البحثبوردة قاصدة بوشري هي مجموعة من الآيات التي تمدح النبي محمد. قصيدة بوردة هي إحدى مؤلفات الإمام البوشيري، فهو أقدم قصيدة بعد توقف طويل جداً. تتم قراءة قصيدة بوردة وغنائها على نطاق واسع في جميع أنحاء العالم الإسلامي. وعادة ما تتخلل قراءة القصيدة صلوات وآيات إضافية. واختيار الإلقاء للكلمات المستعملة في هذا القصيده يجعل من هذه القصيده جميله. لذلك، فإن عبادة كاسيدا تحظى بإعجاب كبير من قبل الصوفيين وغيرهم من المسلمين. بصرف النظر عن ذلك، فإن المعاني العديدة للمصطلحات المستخدمة في هذه القصيدة تجعل الباحثين مهتمين بمعرفة المعنى الأصلي الوارد في هذه القصيدة. والهدف من هذا البحث هو معرفة معنى الاصطلاحات الواردة في كل آية من آيات قاصدة بوردة بوشيري. نوع وطريقة البحث المستخدمة نوعية مع طرق تحليل النص لمراجعة آية عبادة القصيداء من حيث المعنى الاصطلاحي. نتائج هذا البحث هي أنه في قاصدة بوردة من الفصول ١ إلى الفصل ١٠، وجد الباحثون أن هناك ٩٩ معنى من العبارات.